Infrastructure investments in Eastern Neighbours and Central Asia (ENCA) - Olga Kravets (European Investment Bank (EIB), 2013)
Infrastructure in the Eastern Neighbours and Central Asia (ENCA) lags behind other regions in terms of the quality of service provision and this is a potentially important constraint on the achievement of higher economic growth. The purpose of this paper is to examine the recent developments in infrastructure finance drawing together data from national sources, international institutions and project databases. With a total investment in infrastructure over the last decade of over 2.5% of GDP in ENCA as a whole, the paper describes the sources and uses of these funds including the continuing importance finance from the public sector and the recent growth of project finance.
Keywords: 330